Histone methyltransferase Suv39h1 deficiency prevents Myc‐induced chromosomal instability in murine myeloid leukemias1. Issue 4 (23rd January 2013) - Vajen, Beate; Modlich, Ute; Schienke, Andrea; Wolf, Susanne; Skawran, Britta; Hofmann, Winfried; Büsche, Guntram; Kreipe, Hans; Baum, Christopher; Santos‐Barriopedro, Irene; Vaquero, Alejandro; Schlegelberger, Brigitte; et al.
Abstract Suv39h1 mediates heterochromatin formation in pericentric and telomeric regions by trimethylation of lysine 9 of histone 3 (H3K9me3). Yet, its role in the induction of chromosomal instability is poorly understood. We established a leukemia model by retrovirally expressing Myc in wild‐type and histone methyltransferase Suv39h1‐deficient hematopoietic cells and characterized the resulting leukemias for chromosomal instability. All mice that received cells overexpressing Myc developed myeloid leukemia with a median survival of 44 days posttransplantation. Myc‐overexpressing wild‐type leukemias demonstrated clones with numerical chromosomal aberrations (5/16). In secondary transplantations of these leukemic cells, structural changes, mostly end‐to‐end fusions of chromosomes, appeared (10/12). In contrast, leukemic cells overexpressing Myc with reduced or no Suv39h1 expression had a normal karyotype in primary, secondary, and tertiary transplantations (16/16). Myc‐transduced Suv39h1‐deficient cells showed less critically short telomeres (P < 0.05) compared with Myc‐transduced wild‐type bone marrow cells. Gene expression analysis showed upregulation of genes involved in the alternative lengthening of telomeres (ALT) mechanism. Thus, we hypothesize that loss of Suv39h1 implies activation of the ALT mechanism, in turn ensuring telomere length and stability. Our data show for the first time that Suv39h1 deficiency may prevent chromosomal instability by more efficient telomere stabilization in hematopoietic bone marrow cells overexpressing Myc. © 2013 Wiley Periodicals, Inc.